Brazilian Informatics Policy: What Price Sovereignty? - Johnson, Jean (Tufts Archival Research Center, 2005)
Volume 9, Issue 2. Summer In recent years, Brazil has developed an advanced technological base and a strong computer and data services sector. Recent policies aimed at protecting its domestic market put it in direct conflict with U.S. policies which seek to open foreign markets to U.S. exports and investment opportunities. In this article, Jean Johnson examines how Brazil's concern for its national security, technological independence, and development into an "information society" has led to the imposition of a policy of strict protection for Brazil's computer, or informatics, industry for at least the next eight years. Although the policy stems from legitimate concerns about the need to preserve Brazil's sovereignty, and to further its economic development, there are considerable obstacles in the way of its success. Nevertheless, Brazil does have a strong political commitment to see it succeed, and as Ms. Johnson advises that strident opposition from the U.S. may only exacerbate the already strained diplomatic relations between the two countries. A successful Brazilian effort to promote its technological and economic development will benefit U.S. interest in the long run, she concludes.